Growth-at-Risk Is Investment-at-Risk - Amburgey, Aaron J.; McCracken, Michael W. (The Review of Economics and Statistics, 2026)
Abstract We investigate the role financial conditions play in the composition of U.S. growth-at-risk. We document that, by a wide margin, growth-at-risk is investment-at-risk. That is, if financial conditions indicate U.S. real GDP growth will be in the lower tail of its conditional distribution, we know that quantitatively, the main contributor is a decline in investment. Consumption contributes under extreme financial stress. Government spending and net exports do not play a role. We show that leverage plays a key role in determining both consumption- and investment-at-risk, which provides support to the financial accelerator mechanism proposed by Bernanke et al. (1999).